2003
DOI: 10.1002/eji.200323923
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP increases endogenous granulocyte colony‐stimulating factor formation in monocytes and THP‐1 macrophages despite attenuated TNF‐α formation

Abstract: The cytokine granulocyte colony-stimulating factor (G-CSF) is in broad clinical use to treat neutropenia, and trials on its use in immunosuppressed conditions and infections are ongoing. To apply G-CSF effectively, it is crucial to understand the regulation and distribution of its endogenous formation. Since G-CSF release is mediated, at least in part, by TNF- § formation, we investigated whether drugs suppressing TNF- § also impair G-CSF production. Surprisingly, G-CSF formation was enhanced in lipopolysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Then, which cell type is responsible for the G-CSF production, resident macrophages, or the newly elicited neutrophils? We found that in the murine resident peritoneal macrophages, PGE 2 augmented LPS-induced G-CSF production as Hareng et al (13) reported for THP-1 cells. However, in the case of the macrophages, EP4 is responsible for the PGE 2 potentiation of G-CSF release because an EP4 agonist mimicked the effect of PGE 2 more effectively than an EP2 agonist (D. Mori, S. Tsuchiya, and Y. Sugimoto, unpublished observation).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Then, which cell type is responsible for the G-CSF production, resident macrophages, or the newly elicited neutrophils? We found that in the murine resident peritoneal macrophages, PGE 2 augmented LPS-induced G-CSF production as Hareng et al (13) reported for THP-1 cells. However, in the case of the macrophages, EP4 is responsible for the PGE 2 potentiation of G-CSF release because an EP4 agonist mimicked the effect of PGE 2 more effectively than an EP2 agonist (D. Mori, S. Tsuchiya, and Y. Sugimoto, unpublished observation).…”
Section: Discussionsupporting
confidence: 87%
“…PGE 2 in most cases promotes or inhibits the production of cytokines and chemokines induced by stimuli such as LPS or TNF-␣ and thus has been considered to be a modulator of immune responses (30). Indeed, it has been shown that endogenous PGE 2 contributes to LPS-induced G-CSF gene expression in monocytes (12,13). Hareng et al (13) recently demonstrated that dbcAMP enhances LPS-primed promoter activity via a cAMP-responsive element located at Ϫ240 bp of the G-CSF gene in THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclic AMP signaling is also demonstrated to induce IL-6 and granulocyte colony-stimulating factor, possibly through prostaglandin (PG)E2-mediated autoregulation (17,18). The cAMPmediated induction of these genes is PKA-dependent and involves binding of CRE-binding protein and CAAT/enhancer binding protein transcription factors to the genetic promoter elements (17,19).…”
Section: Camp Regulates the Production Of Inflammatory Mediatorsmentioning
confidence: 97%